Conservative management of retinoblastoma: Challenging orthodoxy without compromising the state of metastatic grace. "Alive, with good vision and no comorbidity". (November 2019) - Munier, Francis L.; Beck-Popovic, Maja; Chantada, Guillermo L.; Cobrinik, David; Kivelä, Tero T.; Lohmann, Dietmar; Maeder, Philippe; Moll, Annette C.; Carcaboso, Angel Montero; Moulin, Alexandre; Schaiquevich, Paula; Bergin, Ciara; et al.
Abstract: Retinoblastoma is lethal by metastasis if left untreated, so the primary goal of therapy is to preserve life, with ocular survival, visual preservation and quality of life as secondary aims. Historically, enucleation was the first successful therapeutic approach to decrease mortality, followed over 100 years ago by the first eye salvage attempts with radiotherapy. This led to the empiric delineation of a window for conservative management subject to a "state of metastatic grace" never to be violated. Over the last two decades, conservative management of retinoblastoma witnessed an impressive acceleration of improvements, culminating in two major paradigm shifts in therapeutic strategy. Firstly, the introduction of systemic chemotherapy and focal treatments in the late 1990s enabled radiotherapy to be progressively abandoned. Around 10 years later, the advent of chemotherapy in situ, with the capitalization of new routes of targeted drug delivery, namely intra-arterial, intravitreal and now intracameral injections, allowed significant increase in eye preservation rate, definitive eradication of radiotherapy and reduction of systemic chemotherapy. Here we intend to review the relevant knowledge susceptible to improve the conservative management of retinoblastoma in compliance with the "state of metastatic grace", with particular attention to (i) reviewing how new imaging modalities impact the frontiers of conservative management, (ii) dissecting retinoblastoma genesis, growth patterns, and intraocular routes of tumor propagation, (iii) assessing major therapeutic changes and trends, (iv) proposing a classification of relapsing retinoblastoma, (v) examining treatable/preventable disease-related or treatment-induced complications, and (vi) appraising new therapeutic targets and concepts, as well as liquid biopsy potentiality.